Trauma in Pregnancy: An Underappreciated Cause of Maternal Death. Issue 3 (September 2018) - Kilpatrick, S.J.
Abstract : ( Am J Obstet Gynecol 2017;217:499–500) While the maternal mortality ratio (MMR) drastically decreased from 1917 to 1980, the MMR in the United States has been steadily on the rise since 1980. Increased obesity, high maternal age, higher cesarean section rate and other factors may contribute to this increase. Currently, deaths from trauma in pregnant women are not counted in the MMR or pregnancy-related maternal death statistics and therefore many deaths are not captured.